UK’s Free Trade Agreements with Non-EU Countries: the Case of the Black Sea Region - Shevchenko, Yuliia (Bulgarian Journal of International Economics and Politics, 2021)
With the end of the Brexit transition period and its final departure from the EU, the United Kingdom lost its access to the EU trade agreements that its economy had previously benefited from. Therefore, the UK has been determined to preserve the preferential trading terms with states and trading blocs that used to be covered during its membership in the EU, and introduced a number of Free Trade Agreements (FTA) to guarantee a smooth transition both for the UK and non-EU countries’ economies with which it has extensive trade. The objective is to analyze the signing of Free Trade Agreements between UK and non-EU countries, namely, Georgia, Moldova, Ukraine and Turkey. The methodology is based on comparative case-by-case study. The results indicate that UK’s trade with the countries in Black Sea region (also quite affiliated with the EU) is going to gain more importance, which will broaden the opportunities for the UK become more involved in the economy of the region and, potentially, build stronger and independent political ties with the countries studied.
Keywords: Free Trade Agreements; Brexit; Black Sea Region; Non-EU Member Countries